Effect of free fatty acid on transesterification of waste cooking oil - Lim, H. S.; N. M., Hussin; Gaanty Pragas, Maniam (Penerbit Universiti Malaysia Pahang, 2023)
The presence of high free fatty acids (FFA) in the feedstock is a primary concern in biodiesel production. Waste cooking oil (WCO) is a potential environmentally friendly source, but further research is needed to fully characterize its properties. This study successfully explored the effect of FFA on the transesterification reaction and achieved the conversion of triglycerides in WCO to biodiesel under optimal conditions (molar ratio of oil to methanol 1:9, 2 hours, 65°C, catalyst loading 2.0 wt.% of WCO). The results show that for feedstocks with 0-3% FFA content, methyl ester conversion exceeds 90%, while for feedstocks containing 4-6% FFA, the conversion rate is less than 50%. Biodiesel containing 4–6% FFA undergoes saponification reaction during washing, highlighting the need for pretreatment prior to transesterification. In contrast, 0-3% FFA showed no saponification effect. The physicochemical properties of biodiesel from each FFA% feedstock, including acid value, degree of saponification, viscosity, density, and moisture content, were observed and compared with the ASTM D6751 standard. The results show that the acid value is directly proportional to FFA%, while the saponification value is inversely proportional. This study found that other properties such as viscosity, density, and moisture content were not related to biodiesel quality. In contrast, saponification value testing and GC analysis highlighted the impact of FFA percentage in the feedstock on biodiesel production.